Application of Literacy and Public Speaking to MTS Project Kandenpag Students - Irvan, Rezaldy Azhary (Edumaniora : Jurnal Pendidikan dan Humaniora, 2022)
The Independent Real Work Lecture apprenticeship activity took place in District Yos Sudarso, KM 13.5, Medan City Regency and specifically at the Madrasah Tsanawiyah Project. The main activity carried out is Literacy to improve students' reading and speaking skills including Al-Qur'an literacy for Madrasah Tsanawiyah Project Kandepag students where students are given an understanding of reading the Qur'an with the correct makharijul letters and public speaking training in public speaking well so that it can be applied in everyday life, ending with the implementation of three-language speech by MTS students